A matter of trust. Issue 5 (May 2019) - Gordon, Scott
Abstract : As identity becomes the new perimeter, there is an ongoing trend that suggests that a 'zero trust' security model can augment conventional firewalls and VPNs to fortify an organisation's security posture. This movement towards more available access but with dynamic authorisation is growing as IT becomes more hybrid and applications migrate to the cloud. Prior requirements of forcing users to go through the corporate network – for example, using simple two-factor authentication registration – will change as well. This movement towards more available access but with dynamic authorisation is growing as IT becomes more hybrid and applications migrate to the cloud. Prior requirements of forcing users to go through the corporate network will change as well. And software defined perimeter (SDP) technology can deliver the new trust models we need, argues Scott Gordon of Pulse Secure.